Additive manufacturing of high-strength CrMnFeCoNi-based High Entropy Alloys with TiC addition. (June 2019) - Amar, Abdukadir; Li, Jinfeng; Xiang, Shuo; Liu, Xue; Zhou, Yuzhao; Le, Guomin; Wang, Xiaoying; Qu, Fengsheng; Ma, Shiyu; Dong, Wumei; Li, Qiang
Abstract: High-strength CrMnFeCoNi-based High Entropy Alloys have been developed by laser melting deposition, in which tensile properties of them could be adjusted by controlling the quantity of the TiC addition. The CrMnFeCoNi high entropy alloy with 5 wt% TiC addition has exhibited 723 MPa tensile strength and 32% tensile strain. The improvement in mechanical property is attributed to the introduction of micron TiC reinforced phase, which could promote hinder the propagation of slip bands. Highlights: High entropy alloy with different TiC addition have been synthesized by laser melting deposition. The tensile properties of HEA could be adjusted by controlling the quantity of the TiC addition. The HEA with 5 wt% TiC addition showed a tensile strength of 723 MPa and a tensile strain of 32%.